2001
DOI: 10.1002/jsfa.869
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heating temperature, pH, concentration and starch/whey protein ratio on the viscoelastic properties of corn starch/whey protein mixed gels

Abstract: The viscoelastic properties of corn starch (CS) gels were more dependent on heating temperature, while the properties of whey protein isolate (WPI) gels were more dependent on pH. Thus heating temperature (75, 85, 95°C) and pH (5, 7, 9) were varied to obtain a series of mixed gels with interesting viscoelastic properties. WPI gels showed extensive stress relaxation (SR) indicative of a highly transient network structure, while CS gels relaxed very little in 2000 s. Based on SR results, it appeared that CS/WPI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
65
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 22 publications
7
65
0
4
Order By: Relevance
“…The main factor in this study that could influence and dominate the structural changes in WP was extrusion pH. Hudson and Daubert (2002), and Shim and Mulvaney (2001) indicated that changes in WP structure were significantly dependent on pH while starch was relatively insensitive to pH changes. The extrusion process was more severe in alkaline than in acidic conditions.…”
Section: General Observation On Twpc Productionmentioning
confidence: 93%
See 2 more Smart Citations
“…The main factor in this study that could influence and dominate the structural changes in WP was extrusion pH. Hudson and Daubert (2002), and Shim and Mulvaney (2001) indicated that changes in WP structure were significantly dependent on pH while starch was relatively insensitive to pH changes. The extrusion process was more severe in alkaline than in acidic conditions.…”
Section: General Observation On Twpc Productionmentioning
confidence: 93%
“…It was reported that the absolute difference between G 0 and G 00 over a range of frequencies and the degree of frequency independency of moduli demonstrated the typical characteristics of gels (Clark, 1998;Rodd, Davis, Dunstan, Forrest, & Boger, 2000;Shim & Mulvaney, 2001). Table 3 shows the frequency dependence of the moduli (G 0 and G 00 ) analyzed quantitatively by fitting simple power law relationships…”
Section: Viscoelastic Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…pressure and specific mechanical energy) have also been reported. During heat-moisture-shear-(pressure) treatments as obtained in extrusion, starch and protein can respectively be gelatinised and denatured, with the possibility of starch-protein complexes (Allen, Carpenter, & Walsh, 2007;Matthey & Hanna, 1997;Schmitt, Sanchez, DesobryBanon, & Hardy, 1998;Shim & Mulvaney, 2001;Zhang, Maladen, & Hamaker, 2003). These transformations influence digestibility of starch, protein and their mixtures, and although in vitro protein digestibility of whey fortified foods has been reported (e.g.…”
Section: Introductionmentioning
confidence: 96%
“…Although complex modulus decreased in the presence of WPI (weakened gel structure), it increased as WPI was increased, and this was related to increased enhancement of hydrophobic interactions. In studies of heated mixed WPI and regular or cross-linked waxy maize starch dispersions at pH 7, Shim and Mulvaney (2001) and Ravindra et al (2004) identified three phase-separated networks depending on the composition of the blend; a WPI continuous network weakened by dispersed phase of starch granules when WPI fraction > 60% (WPIdominated), two continuous phases (20% < WPI < 75%), and a starch continuous phase weakened by WPI aggregates when WPI < 20% (starch-dominated). While Champenois et al (1998) found the storage and loss moduli of gluten-starch dispersions (6 -30%) to increase with an increase in starch content, Shim and Mulvaney measured the complex modulus of 100% WPI to be greater than that of 100% starch (0% WPI), while at 5% or 15% total solids, the modulus exhibited a quadratic relationship with WPI content.…”
Section: Introductionmentioning
confidence: 99%